Care as the backbone of a new economy - Carrasco Bengoa, Cristina (Cuadernos de Relaciones Laborales, 2013)
This article presents three ideas that underpin, from our perspective, feminist economics: the theoretical break with the official economy to expand the boundaries beyond the market, the “discovery” of care and the political challenge by proposing a break with the current model. The aim is to show the theoretical and political potential of feminist economics, their ability to propose a new paradigm capable of providing a radiograph of social and economic founding much closer to reality than that provided by the economy.
Keywords: feminist economics; care; living conditions